A radiation-free mixed-reality training environment and assessment concept for C-arm-based surgery - Stefan, Philipp; Habert, Severine; Winkler, Alexander; Lazarovici, Marc; Fuermetz, Julian; Eck, Ulrich; Navab, Nassir (International Journal of Computer Assisted Radiology and Surgery, 2018)
Purpose: The discrepancy of continuously decreasing opportunities for clinical training and assessment and the increasing complexity of interventions in surgery has led to the development of different training and assessment options like anatomical models, computer-based simulators or cadaver trainings. However, trainees, following training, assessment and ultimately performing patient treatment, still face a steep learning curve. Methods: To address this problem for C-arm-based surgery, we introduce a realistic radiation-free simulation system that combines patient-based 3D printed anatomy and simulated X-ray imaging using a physical C-arm. To explore the fidelity and usefulness of the proposed mixed-reality system for training and assessment, we conducted a user study with six surgical experts performing a facet joint injection on the simulator. Results: In a technical evaluation, we show that our system simulates X-ray images accurately with an RMSE of 1.85 mm compared to real X-ray imaging. The participants expressed agreement with the overall realism of the simulation, the usefulness of the system for assessment and strong agreement with the usefulness of such a mixed-reality system for training of novices and experts. In a quantitative analysis, we furthermore evaluated the suitability of the system for the assessment of surgical skills and gather preliminary evidence for validity. Conclusion: The proposed mixed-reality simulation system facilitates a transition to C-arm-based surgery and has the potential to complement or even replace large parts of cadaver training, to provide a safe assessment environment and to reduce the risk for errors when proceeding to patient treatment. We propose an assessment concept and outline the steps necessary to expand the system into a test instrument that provides reliable and justified assessments scores indicative of surgical proficiency with sufficient evidence for validity.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Assessment; C-arm-based spine surgery simulation; Computer aided interventions; Mixed-reality simulation; Training